Makna Ungkapan “Akulah” Dalam Injil Yohanes: Kajian Kristologis dan Soteriologis - Yanto Sandy Tjang; Laurentius Prasetyo (STIKAS Santo Yohanes Salib Kalimantan Barat, 2026)
The expression “I am” (egō eimi) constitutes one of the most distinctive and theologically significant elements in the Gospel of John and plays a central role in the revelation of Jesus’ identity. Far from functioning merely as a linguistic marker of self-identification, this expression serves as a medium of self-revelation through which Jesus discloses His relationship with God and the salvific meaning of His mission for humanity. This study aims to examine the theological significance of the “I am” sayings in the Gospel of John by exploring their biblical context, their roots in Old Testament tradition, and their christological and soteriological implications. Employing a qualitative approach through library research, this study applies an exegetical–theological method to the Johannine text, supported by relevant biblical-theological and exegetical literature. The findings indicate that the “I am” sayings with predicates portray Jesus’ role in the work of salvation through symbolic and relational language, while the absolute (without predicate) “I am” sayings explicitly affirm Jesus’ divine identity by echoing the revelation of the divine name in the Old Testament tradition. Consequently, the Gospel of John presents a high-level Christology that situates Jesus as the center of divine revelation and the source of salvation. This study affirms that the “I am” sayings carry not only doctrinal significance but also existential implications, inviting a response of faith and a lived relationship with Christ in the contemporary life of believers.